Effect of Tangeritin Against Cyclophosphamide-Induced Toxicity in the Larvae of Transgenic Drosophila melanogaster (hsp70-lac Z) Bg9. (2nd November 2018) - Fatima, Ambreen; Khanam, Saba; Jyoti, Smita; Naz, Falaq; Rahul,; Beg, Tanveer; Siddique, Yasir Hasan
ABSTRACT: Tangeritin is a pentamethoxy flavone found in tangerine and other citrus peels. The present study was conducted to study the effect of various doses of tangeritin on the toxic effects induced by cyclophosphamide (CP) in the third instar larvae of transgenic Drosophila melanogaster (hsp70-lacZ)Bg 9 . Commercially available tangeritin and CP were used. CP was used alone at 20 µM of food concentration and with 20, 40, and 80 µM of tangeritin. The exposure of the third instar larvae to 20µM of cyclophosphamide alone results in significant hsp 70 expression along with tissue, DNA, and oxidative damage. The exposure of the third instar larvae to 20 µM of CP along with 20, 40, and 80 µM of tangeritin results in a dose-dependent decrease not only in hsp 70 expression but also in tissue, DNA, and oxidative damage. The results of the present study suggest that tangeritin has a protective role against the toxic effects of cyclophosphamide in the third instar larvae of transgenic Drosophila melanogaster (hsp 70-lac Z)Bg 9 .